Pontine gaze deviation and face turn relieved by eye muscle surgery - Turkcuoglu, Peykan; Aydemir, Orhan; Ozturkmen, Cem; Yildirim, Hanefi (Lippincott Williams & Wilkins, 2008)
A 34-year-old woman developed a bilateral horizontal gaze palsy, left gaze deviation, and right face turn consequent to a pontine hemorrhage. A bilateral horizontal recession and resection of extraocular muscles in both eyes (Parks procedure) eliminated the gaze deviation and face turn. This is the first reported case in which this procedure was used to correct a face turn in a patient with bilateral horizontal gaze palsy but without ocular misalignment.
Keywords: Paralysis